THE INFLUENCE OF PERCEIVED VALUE, IDENTITY, AND SELF-CONGRUITY ON AQUA LIFE PURCHASE INTENTION - Yokie Radnan Kristiyono; Wanda Anjani (Jurnal Manajemen, 2020)
Environmental friendly efforts are a major thing that is important and must be applied in our life. AQUA LIFE is one of the product innovations made by PT. Tirta Investama to support environmentally friendly actions. This research was conducted to examine the consumer behavior of purchase intentions regarding identity and self congruity to Green Marketing with the Perceived Value that has been offered. The study was conducted for three months by collecting data using a questionnaire, then it was analyzed using SmartPLS v. 3.3.2 using validity, reliability, and common method bias in the pre-test and actual test. The result showed that the overall T-statistics and P-Value met the rule of thumb, >1.96 and <0.05 explains that consumers are interested in buying AQUA LIFE with the product concept and packaging that are offered with an environmental-friendly concept, and they have experienced a Green Perceived Value. Consumers are aware of and want AQUA LIFE to fulfill their needs in accordance with their identity and self congruity